Effect of food availability on the growth and age determination of European sardine (Sardina pilchardus Walbaum, 1792) larvae. (3rd May 2021) - Garrido, Susana; Ferreira, Susana; Soares, Claudia; Meneses, Isabel; Baylina, Nuria; Batista, Hugo; Teodósio, Maria Alexandra; Piecho-Santos, António Miguel; Ré, Pedro
Abstract: Accurate assessment of age and growth of fish is essential to understand population dynamics, namely for age-structured stock assessment and for determining vital rates of fish (e.g. age at sexual maturity) and their relationship with environmental variability. To validate the daily deposition in the otoliths of European sardine ( Sardina pilchardus ) larvae, these were reared with a range of food densities translating into feeding rates extending from less than required for maintenance to saturated feeding levels. When exogenous feeding began, a high variability in the relationship between number of growth increments (GI) and elapsed days after hatching (dph) was observed, irrespective of the feeding treatment. GI counts using a light microscope were less than one per day for larvae <15 dph (ranging from 0.17–0.43 GI day −1 ) and similar for larvae reared with different food concentrations. The rate of GI count vs age was significantly higher for larvae older than 15 dph. GI count from 3–30 dph was lower than one per day (0.45–0.75 GI day −1 95% CI) for fed larvae 3–30 dph. Scanning electron microscopy confirmed the daily deposition of GI and revealed some increment widths around 0.2 μm, particularly during the first week post-hatch. Otoliths of wild sardine larvae exhibited narrow GI (<0.5 μm) comparable with reared larvae. This study demonstrates that during the first weeks after hatch the daily increment deposition is underestimated using traditional light microscopy, which must be taken into account in future works determining wild sardine larval growth.